Improved inhibition of telomerase by short twisted intercalating nucleic acids under molecular crowding conditions - Agarwal, Tani; Pradhan, Devranjan; Geci, Imrich; El-Madani, Amro M.; Petersen, Michael; Pedersen, Erik B.; Maiti, Souvik (Nucleic Acid Therapeutics, 2012)
Human telomeric DNA has the ability to fold into a 4-stranded G-quadruplex structure. Several G-quadruplex ligands are known to stabilize the structure and thereby inhibit telomerase activity. Such ligands have demonstrated efficient telomerase inhibition in dilute conditions, but under molecular crowding conditions mimicking physiological milieu, stabilization of the telomeric G-quadruplex is often lost. We attempted to demonstrate the enhanced G-quadruplex stabilizing ability under molecular conditions by using twisted intercalating nucleic acids (TINA)-modified oligonucleotides. We have shown using circular dichroism and ultraviolet spectroscopic methods that these TINA-modified short oligonucleotides function as G-quadruplex, inducing agents and participate in the formation of stabilized 3:1 G-quadruplex with the human telomeric oligonucleotide. Using enzyme-linked immunosorbent assay-based telomerase repeat amplification assay (TRAP) assay as well as nondenaturing polyacrylamide gel electrophoresis-based TRAP, we demonstrate remarkable enhancement in their anti-telomerase activity even under molecular crowding conditions. This is the first time in which a G-quadruplex stabilizing agent has demonstrated enhanced activity even under molecular crowding conditions.

In the sense of transcription regulation by G-quadruplexes: asymmetric effects in sense and antisense strands - Agarwal, Tani; Roy, Saumya; Kumar, Santosh; Chakraborty, Tushar Kanti; Maiti, Souvik (Biochemistry, 2014)
G-Quadruplexes occupy important regulatory regions in the genome. DNA G-quadruplexes in the promoter regions and RNA quadruplexes in the UTRs (untranslated regions) have been individually studied and variously implicated at different regulatory levels of gene expression. However, the formation of G-quadruplexes in the sense and antisense strands and their corresponding roles in gene regulation have not been studied in much detail. In the present study, we have elucidated the effect of strand asymmetry in this context. Using biophysical methods, we have demonstrated the formation of stable G-quadruplex structure in vitro using CD and UV melting. Additionally, ITC was employed to demonstrate that a previously reported selective G-quadruplex ligand was able to bind and stabilize the G-quadruplex in the present sequence. Further, we have shown using reporter constructs that although the DNA G-quadruplex in either strand can reduce translation efficiency, transcriptional regulation differs when G-quadruplex is present in the sense or antisense strand. We demonstrate that the G-quadruplex motif in the antisense strand substantially inhibits transcription, while when in the sense strand, it does not affect transcription, although it does ultimately reduce translation. Further, it is also shown that the G-quadruplex stabilizing ligand can enhance this asymmetric transcription regulation as a result of the increased stabilization of the G-quadruplex.